Resistance induction and nematicidal activity of certain monoterpenes against tomato root-knot caused by Meloidogyne incognita - Elsharkawy, Mohsen Mohamed; Al-Askar, Abdulaziz A.; Behiry, Said I.; Abdelkhalek, Ahmed; Saleem, Muhammad Hamzah; Kamran, Muhammad; Derbalah, Aly (Frontiers in Plant Science, 2022)
Abstract This research was performed to evaluate the potential of carvone, cuminaldehyde, cineole, and linalool for the control of root-knot of tomato. The tested control agents were evaluated for their ability to stimulate systemic resistance to Meloidogyne incognita in tomato by monitoring the transcription levels of defense-related genes. Moreover, the ability of the tested agents to induce nematicidal activity concerning second-stage juveniles (J2) hatching and mortality was evaluated. Furthermore, the effect of the tested agents on certain tomato growth and yield parameters was assessed. The tested monoterpenes showed high nematicidal activity against Meloidogyne incognita concerning J2 hatching inhibition and mortality. Carvone, cuminaldhyde, linalool, and cineole had LC50 values of 123.5, 172.2, 354.9, 466.4, and 952.3 µg/mL, respectively. Carvone was found to be the most efficient hatching inhibitor. The tested monoterpenes showed a high potential against root-knot under greenhouse and field conditions with respect to root-galling, egg masses, and the number of J2. Carvone was the most effective treatment. The growth and yield characters of treated tomato were significantly increased in monoterpenes treatments compared to untreated control. Treated Tomato plants showed expression of defense-related genes (PR1 and PAL) 5-8 folds higher than the control. The results also showed that cuminaldhyde, followed by carvone, linalool, and cineole, had the greatest levels of expression in tomato plants. Taken together, the selected monoterpenes could be used as alternatives to control the root-knot of tomato.